Amr makruf nahi mungkar and social order: How far should moral policing be allowed in modern society? - Ismail, S.Z. (2017)
The objective of this paper is to discuss the true concept of amr makrufnahi mungkar based on shariah and the interpretation of the Muslim scholars, particularly in the light of modern application. According to Ibn Taimiyyah and other scholars, amar makruf nahi mungkar is a collective effort of the people to maintain order in the society and this includes the responsibility of the state as well. Amar makruf nahi mungkar and the concept of hisbah cover both the responsibility of ummah in general as well as the government. In today's society, where individualistic attitude and economic drive are more prevalent than concern for societal wellbeing, the government shows the concern by establishing an institution to enjoining the good and forbidding the wrong. The question is, how far can it be enforced using the legalistic approach? Or, should such effort be limited to societal mechanism involving parents, teachers and community leaders in an informal way? How does we tackle the claims that amar makruf nahi mungkar lead to transgression to privacy, challenging the freedom of expression and targeting moral behavior and manner of female rather than male. Tn Malaysia, the formal hisbali or the work on amar makruf nahi mungkar focuses on Muslims only conducted by Religiou-s Enforcement Unit under State's Religious Department with power and jurisdiction accorded by the law. The paper will be focused on the scope it can be applied in the current situation and then discusses the challenges of that duty in the Malaysian society today.